2022
DOI: 10.3390/d14121048
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant and Antimicrobial Effects of Essential Oils Extracted from Two New Ocimum basilicum L. Varieties

Abstract: Recent agricultural research aims to identify novel applications for plant extracts as efficient defenses against weeds, insects, or phytopathogenic agents. The main goal of the present study was to evaluate two new varieties of basil (Ocimum basilicum L., fam. Lamiaceae), Yellow basil, “Aromat de Buzau” variety and Red-violet basil, “Serafim” variety. The basil varieties were studied under different aspects regarding biochemical characterization using GC-MS, antioxidant activity evaluated under three methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Poonkodi reported IC50 antioxidant activities of essential oil of Ocimum basilicum from four different studies with the following values 0.96 g/L, 83.54 mg/mL, 25 μg/mL, 4.8-6.7 μg/mL, and percentage inhibition of two other research investigations as 55.67± 3.38 and 92.5-94.6%. In a similar study, the antioxidant activity of Ocimum basilicum essential oil against DPPH assay showed IC50 values of 15.47± 0.5 0 and 0.85 ± 0.01 g/L, respectively, for the Yellow basil (Aromat de Buzau) and Red-violet basil (Serafim) varieties of the plant investigated [33]. Furthermore, Ocimum basilicum essential oil extracted by SFME exhibited a dose-dependent increase with a radical scavenging activity of 86.13 ± 2.8% at 20 mg/mL, which is higher than the DPPH % inhibition of the Ocimum basilicum essential oil extracted by HD with values of 76.13 ± 2.6%, at the same concentration [35].…”
Section: Percentage Inhibition Of Dpph Free Radical By Essential Oils...mentioning
confidence: 71%
See 1 more Smart Citation
“…Poonkodi reported IC50 antioxidant activities of essential oil of Ocimum basilicum from four different studies with the following values 0.96 g/L, 83.54 mg/mL, 25 μg/mL, 4.8-6.7 μg/mL, and percentage inhibition of two other research investigations as 55.67± 3.38 and 92.5-94.6%. In a similar study, the antioxidant activity of Ocimum basilicum essential oil against DPPH assay showed IC50 values of 15.47± 0.5 0 and 0.85 ± 0.01 g/L, respectively, for the Yellow basil (Aromat de Buzau) and Red-violet basil (Serafim) varieties of the plant investigated [33]. Furthermore, Ocimum basilicum essential oil extracted by SFME exhibited a dose-dependent increase with a radical scavenging activity of 86.13 ± 2.8% at 20 mg/mL, which is higher than the DPPH % inhibition of the Ocimum basilicum essential oil extracted by HD with values of 76.13 ± 2.6%, at the same concentration [35].…”
Section: Percentage Inhibition Of Dpph Free Radical By Essential Oils...mentioning
confidence: 71%
“…Ocimum basilicum varieties, Yellow basil and Red-violet basil, were characterized by high concentrations of linalool, accounting for 32.66 % and 52.18 % of the respective compositions, compared to the other compounds[33].…”
mentioning
confidence: 99%
“…Nakamura et al42 have reported 750 and 1500 µg/ml of O. gratissimum essential oil as MIC for Candida albicans and Candida tropicalis, respectively. Furthermore, according to the results reported by Stan (Tudora) et al43 , the inhibitory activity of O. gratissimum against Botrytis cinerea and F. oxysporum is higher than that of Ocimum basilicum. These differences can be explained by chemical composition related to the geographical location of the plant.…”
mentioning
confidence: 64%
“…Parameter/Parameters Minyak atsiri kemangi mengandung berbagai senyawa terpen dan terpenoid yang memiliki aktivitas antimikroba tinggi. Senyawa seperti linalool dan estragol bersifat lipofilik sehingga mudah masuk ke protoplasma dari sel bakteri dan membran sel jamur dan berinteraksi dengan lapisan fosfolipid hingga polisakarida pada sel mikroba yang menyebabkan permeabilitas membran terganggu, kehilangan ionion, serta beberapa kandungan dalam sel yang dapat berujung pada kematian sel (Stan Tudora) et al, 2022;Waller et al, 2017). Kombinasi kitosan dan minyak atsiri juga didapati mampu menyebabkan kerusakan dinding sel kitin jamur yang ditunjukkan dengan kenampakan hifa jamur yang tidak berwarna setelah dilakukan pewarnaan kitin pada dinding sel dengan larutan lactophenol cotton blue (Sheikh et al, 2021).…”
Section: Perlakuan/ Treatmentsunclassified